Bar-shaped steel material and production method thereof

A bar-shaped steel material with controlled hardness and grain size, produced via specific rolling processes, addresses deformation anisotropy issues in forging, enabling cost-effective and environmentally friendly manufacturing of mechanical parts.

JP2024177784AActive Publication Date: 2024-12-24SANYO SPECIAL STEEL CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2023096117
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

Existing steel materials for mechanical parts in transportation and industrial machinery face challenges in reducing deformation anisotropy during forging, leading to the need for additional processes like annealing and cutting to achieve dimensional accuracy, which increases costs and environmental impact.

Method used

A bar-shaped steel material with controlled hardness distribution and grain size, characterized by specific hardness relationships and a predominantly ferrite-pearlite structure, is produced through controlled rolling and finishing processes to minimize deformation anisotropy, allowing omission of annealing and cutting.

Benefits of technology

The solution results in reduced deformation anisotropy, maintaining dimensional accuracy without additional processing steps, thereby reducing manufacturing costs and environmental emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177784000001_ABST
    Figure 2024177784000001_ABST
Patent Text Reader

Abstract

To provide a bar-shaped steel material excellent in deformation anisotropy in compression processing.SOLUTION: On a straight line passing through a center of an optional cross section orthogonal to a longer direction of a bar-shaped steel material, maximum hardness A (HRB) as a maximum value of the hardness on a first straight line extending from the center to the steel material surface in one direction, maximum hardness B (HRB) as a maximum value of the hardness on a second straight line extending from the center to the steel material surface in a direction opposite to the first straight line, and hardness C (HRB) at the center satisfy a relation in a following formula (1), and average hardness in the optional cross section is 93 HRB or less: |(C-A)-(C-B)|≤4.0 HRB (1).SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a rod-shaped alloy steel material for machine structures used as a material for machine parts such as gears and shafts in transport equipment such as automobiles and industrial machinery such as construction machinery. [Background technology]

[0002] In order to impart strength and wear resistance to mechanical parts used in transportation equipment and industrial machinery, bar-shaped steel materials are processed into a desired shape by plastic processing or the like, and then heat treatment is performed to harden the surface by carburizing, nitriding, carbonitriding, or the like. These mechanical parts are usually made of alloy steel materials for mechanical structures, such as chrome steel (SCr), chrome molybdenum steel (SCM), and nickel chrome molybdenum steel (SNCM). In addition, in the forming process, which is a pre-process of the heat treatment, mechanical processing such as forging and cutting is applied. In particular, in forging processing, a process of annealing the material before processing is added to reduce the deformation resistance in order to improve the compressive deformability of the material.

[0003] However, in recent years, in the activities to realize carbon neutrality and reduce manufacturing costs, the omission of the above-mentioned pre-processing annealing has been attempted. In addition, as described above, the main methods for forming a material into a desired shape are forging and cutting, which apply compressive stress to the material, but in this forming process, it is desired to reduce the number of steps in order to achieve further carbon neutrality and reduce manufacturing costs. In particular, cutting is performed on processing areas that do not have the required dimensional accuracy in forging, but if the dimensional accuracy in the forging process can be improved, the cutting process can be omitted. For this reason, it is also desired as a characteristic of steel that the material has low deformation anisotropy when compressive stress, which is the main stress in forging, is applied.

[0004] In order to meet the above demands, Patent Documents 1 to 4 propose materials in which the structure of the material, the average hardness, the standard deviation of the hardness distribution, and the difference between the maximum and minimum hardness values ​​are specified. Of these, Patent Document 4, Japanese Patent No. 4500246, proposes a steel tube-shaped material having a mixed structure of ferrite and pearlite, in which the average hardness value and the difference between the maximum and minimum hardness values ​​are specified. Patent Documents 1 to 3, Japanese Patent No. 4448047, Japanese Patent No. 4464862, and Japanese Patent No. 4464864 propose steel materials in which 80% or more of the entire structure is a mixed structure of ferrite and pearlite, and in which the average hardness value and the standard deviation in the hardness distribution are specified. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4448047 [Patent Document 2] Patent No. 4464862 [Patent Document 3] Patent No. 4464864 [Patent Document 4] Patent No. 4500246 Summary of the Invention [Problem to be solved by the invention]

[0006] In the materials of Patent Documents 1 to 4, the metal structure is a mixed structure of ferrite and pearlite, and the average hardness is low, so that it is possible to omit annealing before forging. However, it is not possible to reduce the deformation anisotropy of the material when compressive stress is applied in forging. Patent Document 4 only specifies the maximum and minimum hardness values, and does not specify the direction of the hardness distribution. In addition, Patent Documents 1 to 3 specify the standard deviation, which is the variation in hardness distribution, but do not specify the direction of the variation, and it is not possible to control the deformation anisotropy when compressive stress is applied.

[0007] Therefore, the present invention is characterized by providing a steel bar having reduced deformation anisotropy when a compressive stress is applied thereto. [Means for solving the problem]

[0008] The present invention relates to a bar-shaped steel material which has been completed as a result of extensive investigations aimed at solving the above-mentioned problems, and details thereof are as follows.

[0009] (1) A bar-shaped steel material, characterized in that, on a line passing through the center of any cross section perpendicular to the longitudinal direction of a bar-shaped steel material, a maximum hardness A (HRB) which is the maximum hardness value on a first line extending from the center in one direction to the surface of the steel material, a maximum hardness B (HRB) which is the maximum hardness value on a second line extending from the center to the surface of the steel material in the opposite direction to the first line, and a hardness C (HRB) at the center satisfy the relationship of the following formula (1), and the average hardness in the any cross section is 93 HRB or less. |(CA)-(CB)|≦4.0HRB (1)

[0010] (2) The bar-shaped steel material according to (1) above, characterized in that the crystal grain size of ferrite in the metal structure of any cross section is 8.0 or more in terms of average grain size number measured in accordance with JIS G 0551.

[0011] (3) The steel bar according to (1) above, wherein the arbitrary cross-sectional shape is circular or rectangular.

[0012] (4) The bar-shaped steel material according to (1) above, characterized in that the steel material is any one of SCr, SCM, and alloy steel with improved hardenability to which Nb has been added.

[0013] (5) The bar-shaped steel material according to (1) above, characterized in that in the metal structure in any cross section, the proportion of ferrite and pearlite structures is 80% or more.

[0014] (6) A method for producing a steel bar according to the above (1), comprising the steps of: A method for manufacturing a bar-shaped steel material, comprising rolling a steel slab with a rolling mill to form an intermediate product, and introducing the intermediate product having a surface temperature of 1000°C or less into a finishing rolling mill to perform finish rolling. Effect of the Invention

[0015] The present invention can provide a steel bar having reduced deformation anisotropy when compressive stress is applied. Since the steel bar of the present invention has excellent deformation anisotropy when compressive stress is applied, cutting after forging can be omitted. In addition, since the annealing step before forging can be omitted, machine parts can be obtained with reduced CO2 emissions and low manufacturing costs. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is a diagram showing a steel bar according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view taken along line aa in FIG. [Diagram 3] FIG. 2 is a diagram showing the shapes of a test sample cut from a bar-shaped steel material before and after compressive stress processing. [Figure 4] FIG. 13 is a diagram showing a steel bar according to another embodiment. [Diagram 5] FIG. 5 is a cross-sectional view taken along line bb in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] This embodiment will be described with reference to the drawings. FIG. 1 shows one embodiment of a bar-shaped steel material 1, which is a bar-shaped steel material. The bar-shaped steel material 1 has a long shape, and FIG. 2 shows a cross section 2 along line aa at an arbitrary position in the longitudinal direction. FIG. 2 is an aa cross section view, and is a diagram explaining the measurement position of the hardness of the cross section in this embodiment. The cross section 2 is a cross section perpendicular to the longitudinal direction of the bar-shaped steel material 1. A line AL, which is a first straight line, and a line BL, which is a second straight line, shown in the cross section 2 of FIG. 2 are on an arbitrary line passing through the center 3 of the circular cross section 2, and extend from the center 3 toward the surface 4 of the bar-shaped steel material 1 in opposite directions to each other.

[0018] In the present embodiment, the hardness of the bar-shaped steel material 1 is measured at the center 3 of an arbitrary cross section 2 perpendicular to the longitudinal direction of the bar-shaped steel material 1, and at arbitrary positions on the line AL and the line BL. The value obtained by performing a predetermined calculation based on the measured values ​​satisfies the condition of the following formula (1). |(CA)-(CB)|≦4.0HRB (1)

[0019] Here, A is the maximum hardness on the straight line AL, B is the maximum hardness on the straight line BL, and C is the hardness at the center 3. The hardnesses A, B, and C are all Rockwell hardness (HRB) (JIS Z2245). The maximum hardness A of AL and the maximum hardness B of BL can be measured at any multiple points on each straight line portion (excluding the position of the center 3) and the maximum hardness can be selected from the measured values. In this embodiment, the hardness is measured at four points and the maximum hardness is extracted. The difference (CA) between the maximum hardness A and the hardness C and the difference (CB) between the maximum hardness B and the hardness C are calculated by the above formula (1), and the absolute value of the difference between these differences is calculated, so that the deformation anisotropy in the compressive deformation of the bar-shaped steel material 1 can be evaluated.

[0020] Figure 3 shows the shapes of test sample 5, which is a sample obtained by cutting the bar-shaped steel material 1 in Figure 1 to an arbitrary length, before compressive stress 6 is applied to stress-applied surface 7 along the longitudinal direction of bar-shaped steel material 1, and post-compression sample 9 after test sample 5 is compressed and deformed by compressive stress 6. In post-compression sample 9, surface 4 is deformed into a drum shape due to the application of compressive stress 6. In post-compression sample 9, post-processing stress-applied surface 10 to which compressive stress 6 is applied and post-processing stress-receiving surface 11 to which compressive stress 6 is received have different post-processing shapes due to the deformation anisotropy for which formula (1) is an index.

[0021] The smaller the deformation anisotropy of the steel material, the closer to similar the shapes of the post-processing stress-applied surface 10 and the post-processing stress-receiving surface 11 to which the compressive stress 6 is applied, respectively, to the shapes of the stress-applied surface 7 and the stress-receiving surface 8 of the test sample 5 before processing. In contrast, the larger the deformation anisotropy of the steel material, the more partially non-similar the shapes of the post-processing stress-applied surface 10 and the post-processing stress-receiving surface 11 of the sample 9 after compression processing become, respectively, compared with the stress-applied surface 7 and the stress-receiving surface 8 of the test sample 5. In other words, when the deformation anisotropy is larger, in the case where the cross-sectional shape of the test sample 5 is circular, the post-processing stress-applied surface 10 and the post-processing stress-receiving surface 11 of the sample 9 after compression processing become shapes non-similar to a circle (for example, an ellipse).

[0022] In this way, if the cross-sectional shape changes to a non-similar shape before and after the application of compressive stress 6, the dimensional accuracy will deteriorate when the machine part is formed by forging, and cutting will be necessary after the forging, making it difficult to omit the cutting process. In contrast, the value of formula (1), which is an index of deformation anisotropy, is 4.0 HRB or less, and the steel material of this embodiment that satisfies the conditions of formula (1) can maintain the desired dimensional accuracy even after the application of compressive stress, as described later in the examples. Therefore, it becomes possible to omit the cutting process after the forging process.

[0023] In addition, the average hardness in the cross section 2 of the bar-shaped steel material 1 of this embodiment is 93 HRB or less in terms of Rockwell hardness. By setting the average hardness of the cross section 2 to 93 HRB or less, the annealing process before the forging process can be omitted. The average hardness is calculated by measuring the hardness at any position in the cross section 2. Specifically, in any randomly determined cross section 2 perpendicular to the longitudinal direction of the bar-shaped steel material 1 (for example, the same surface as the cross section 2 evaluated by the formula (1) may be used, or a different surface), the hardness (HRB) is measured at four points from the position of the surface 4 to a position of D / 4, assuming that the diameter is D. The four points are four positions of D / 4 on two straight lines perpendicular to each other passing through the center 3. The arithmetic average of the measured values ​​at the four points is the average hardness of the cross section of this embodiment. The lower limit of the average hardness of the cross section 2 is not particularly limited, but may be 80 HRB or more.

[0024] In the above embodiment, the case of the bar-shaped steel material 1 having a circular cross section perpendicular to the longitudinal direction has been described, but steel material having other cross-sectional shapes may be used. Fig. 4 shows a bar-shaped steel material 12 of another embodiment. Fig. 5 shows a cross section 13 of the bar-shaped steel material 12 taken along line bb shown in Fig. 4. The cross section 13 is a cross section perpendicular to the longitudinal direction of the bar-shaped steel material 12, and the shape of the cross section 13 is rectangular. The position of the center 3 in such a rectangular cross section 13 can be the point where the diagonal lines 14 intersect.

[0025] In the case of a bar-shaped steel material 12 having a rectangular cross section 13, the straight line for calculating the hardness of the formula (1) may be any straight line that passes through the center 3 where the diagonal line 14 intersects and extends on the surface of the steel material. The arbitrary straight line may be, for example, a diagonal line passing through the center 3, or may be a line other than the diagonal line passing through the center 3. FIG. 5 shows, as an example, a case where the arbitrary straight line is the diagonal line 14. The hardness of the straight line is measured in the same manner as in the case of a steel material having a circular cross section. That is, the hardness is measured at the center 3, on a straight line AL extending from the center 3 to the surface, and on a straight line BL extending on the surface in the opposite direction to the straight line AL. The hardness of the straight lines AL and BL is measured at multiple arbitrary points, and the maximum hardness A on AL and the maximum hardness B on BL may be calculated. The average hardness of the cross section 13 may also be calculated in the same manner as in the case of the circular cross section 2. Specifically, when the length of the diagonal in Fig. 5 is D, the hardness is measured at four points on the two diagonals, which are D / 4 away from each vertex, and the average value is calculated. The cross-sectional shape of the bar-shaped steel material may be a polygon other than a rectangle.

[0026] The material of the steel bar 1 or 12 is carbon steel or alloy steel, and a preferable material is alloy steel for machine structure. Examples of alloy steel for machine structure include SCr and SCM. In addition, alloy steel with improved hardenability, which contains Nb or the like, is also a preferable material as a material with improved hardenability.

[0027] SCr contains 0.12 mass% or more and 0.48 mass% or less of C, 0.15 mass% or more and 0.35 mass% or less of Si, 0.55 mass% or more and 0.95 mass% or less of Mn, 0.030 mass% or less of P, 0.030 mass% or less of S, 0.25 mass% or less of Ni, 0.85 mass% or more and 1.25 mass% or less of Cr, and the remainder being Fe and unavoidable impurities.

[0028] SCM contains 0.12 mass% or more and 0.49 mass% or less of C, 0.15 mass% or more and 0.35 mass% or less of Si, 0.30 mass% or more and 1.00 mass% or less of Mn, 0.030 mass% or less of P, 0.030 mass% or less of S, 0.25 mass% or less of Ni, 0.85 mass% or more and 1.50 mass% or less of Cr, and the remainder is Fe and unavoidable impurities.

[0029] The hardenability improved alloy steel contains 0.14 mass% or more and 0.25 mass% or less of C, 0.25 mass% or more and 0.55 mass% or less of Si, 0.25 mass% or more and 1.55 mass% or less of Mn, 0.020 mass% or less (including 0.00 mass%) of P, 0.020 mass% or less of S, 0.20 mass% or less (including 0.00 mass%) of Ni, 1.50 mass% or more and 3.00 mass% or less of Cr, 0.070 mass% or less (including 0.00 mass%) of Nb, and the balance being Fe and unavoidable impurities.

[0030] In addition, impurities in the chemical composition are components that are mixed in from components contained in raw materials or the manufacturing environment when steel is industrially manufactured, and are components that are acceptable within a range that does not adversely affect the steel of this embodiment.

[0031] The metal structure of the bar-shaped steel material 1 or 12 contains a ferrite + pearlite structure, and it is preferable that the occupancy rate of the ferrite + pearlite structure in the cross-sectional area of ​​any cross section of the steel material is 80% or more. If it is 80% or more, the hardened structure of the metal structure can be reduced, and the hardness of the bar-shaped steel material 1, 12 can be reduced. For example, if the occupancy rate of the ferrite + pearlite structure is 80% or more and the hardness of the steel material cross section is 93 HRB or less, the annealing step before forging can be omitted.

[0032] The grain size of the ferrite in the structure is preferably 8.0 or more in the results of measurement in accordance with JIS G 0551. The average grain size number is calculated based on the measurement results obtained by polishing the cross section of the bar-shaped steel material 1 or 12, subjecting it to nital etching, and measuring the grain size by observation with an optical microscope. If the grain size of the ferrite in the metal structure has an average grain size number of 8.0 or more and a smaller grain size, the deformation anisotropy of the bar-shaped steel material 1 or 12 is reduced, which is preferable. The larger the average grain size number, the smaller the effect of the hardened structure in the microstructure and the smaller the deformation anisotropy, which is preferable, so the grain size of the ferrite in the metal structure is more preferably 9.0 or more.

[0033] The steel bars 1 and 12 are manufactured by rolling, typically by hot rolling. In this manufacturing method, a steel slab is obtained through processes such as refining, ingot casting, and blooming. The steel slab is heated in a heating furnace and subjected to continuous rolling by a rough row rolling mill. This rolling process lengthens the steel slab and reduces its diameter, and an intermediate product is obtained. This intermediate product is further continuously rolled by an intermediate row rolling mill and a finishing row rolling mill (finishing rolling mill). This intermediate product is air-cooled to obtain the steel bars 1 and 12.

[0034] The metal structure of the steel bars 1 and 12 depends greatly on the temperature of the intermediate product in the finishing rolling mill after rolling by a rolling mill such as a roughing mill. By setting this temperature relatively low, steel bars 1 and 12 having a large average grain size number and small anisotropy in hardness distribution can be obtained. Therefore, the surface temperature of the intermediate product when (immediately before) it is introduced into the finishing rolling mill is preferably 1000°C or less, more preferably 980°C or less, and particularly preferably 960°C or less.

[0035] According to the present embodiment, the cross-sectional hardness of the bar-shaped steel material satisfies the condition of the above formula (1) and the average hardness of the cross-section is equal to or less than the above-mentioned predetermined hardness, so that a bar-shaped steel material having smaller deformation anisotropy when compressive stress is applied can be provided. Therefore, by using the bar-shaped steel material of the present embodiment, it is possible to omit cutting after forging. EXAMPLES

[0036] Hereinafter, the embodiments will be described in more detail with reference to examples. The scope of the present disclosure should not be construed as being limited based on the description of these examples.

[0037] First, as an example, SCr420, SCM420, and hardenability improved alloy steel A (steel material A) having the compositions shown in Table 1 were melted, and two steel pieces were obtained for each steel type. These steel pieces were subjected to continuous rolling using a rough row rolling mill, an intermediate row rolling mill, and a finishing row rolling mill to obtain intermediate products. The surface temperature of the intermediate products immediately before being introduced into the finishing row rolling mill was 1000°C for one of the steel pieces ((a) for each steel type in Table 2) and 960°C for the other steel piece ((b) for each steel type in Table 2 below). These intermediate products were air-cooled, and bar-shaped steel materials 1 having a circular cross-sectional shape and a diameter Di of 30 mm were obtained for each steel material.

[0038] As a comparative example, two steel pieces were prepared for each steel type in the same manner as in the examples, and finish rolling was performed with the surface temperature of the intermediate product immediately before being introduced into the finishing train rolling mill being 1100°C for one steel piece ((a) for each steel type in Table 2) and 1150°C for the other steel piece ((b) for each steel type in Table 2). The rest of the process was the same as in Example 1, and bar-shaped steel material 1 was obtained.

[0039] [Table 1]

[0040] A cylindrical test piece was obtained by cutting a bar-shaped steel material 1. This test piece had a diameter of 14 mm and a height of 21 mm. For the cross section of this test piece, the Rockwell hardness (HRB) was measured at the center 3 shown in FIG. 2, and the Rockwell hardness (HRB) was measured at four points on each of the lines AL and BL on an arbitrary line passing through the center 3. Then, the maximum hardness A on the line AL and the maximum hardness B on the line BL were extracted from the measured values, and the absolute value of the hardness distribution on each line was calculated based on the difference with the hardness C at the center 3 shown in formula (1). Then, anisotropy was verified from the results. In addition, when the diameter of the cross section 2 of the test piece is D, the hardness (HRB) was measured at four points at a position of D / 4 from the surface 4 on two perpendicular lines passing through the center 3, and the average value of the arithmetic average was calculated as the cross-sectional average hardness (HRB). Thereafter, the test piece was compressed in the height direction with its ends restrained at a swaging ratio (= (height before processing - height after processing) / height before processing) of 60%.

[0041] The results of measuring the Rockwell hardness and calculating the values ​​of formula (1) are shown in Table 2. In the examples, the values ​​of formula (1) for all the steel test pieces were 4.0HRB or less, satisfying the conditions, but in the comparative examples, all the results exceeded 4.0HRB.

[0042] In addition, to confirm the actual deformation anisotropy due to stress application, the deformation amount on the straight line AL and the deformation amount on the straight line BL after the test piece was compressed were confirmed. Specifically, the length of each straight line was measured from the center position of the cross section of the test piece after compression processing, and the difference F (=|length of straight line AL after processing-length of straight line BL after processing|) was obtained. The straight lines AL and BL used in calculating the difference F are straight lines at the same position as the straight lines AL and BL used to measure the hardness used in formula (1). As a result, as shown in Table 2, in the examples, the difference F of each length was 0.5 mm or less, which was within the normal dimensional tolerance of JIS B 0408 metal pressed products, but in the comparative examples, the difference F exceeded the dimensional tolerance of 1 mm, and even if it did not exceed 1 mm, it was larger than the examples and closer to 1 mm.

[0043] Therefore, it was confirmed that, in the examples, the deformation anisotropy when compressive stress was applied was sufficiently reduced, and cutting after forging could be omitted. On the other hand, in the comparative examples, the dimensional tolerance was large, and cutting was necessary. In addition, the average grain size number of ferrite was 8.0 or more in the examples, but less than 8.0 in the comparative examples. In addition, the average cross-sectional hardness before compression was 93HRB or less in all the examples, and it was confirmed that the annealing step before forging could be omitted. In all the comparative examples, the average cross-sectional hardness was greater than 93HRB.

[0044] [Table 2] [Industrial Applicability]

[0045] The steel bar of the present invention is an optimum steel material for various machine parts that realizes carbon neutrality and reduced manufacturing costs. [Explanation of symbols]

[0046] 1, 12 Steel bars 2. Section 3 Center (of bar steel section) 4. Surface (of steel bar) 5. Test sample 6. Compressive Stress 7 Stress application surface 8 Stress bearing surface 9. Sample after compression processing 10 Stressed surface after processing 11 Stress-receiving surface after processing 13 Section 14 Diagonal AL, BL Straight line passing through the center of the cross section of a bar-shaped steel material

Claims

1. A bar-shaped steel material, characterized in that, on a line passing through the center of any cross section perpendicular to the longitudinal direction of a bar-shaped steel material, a maximum hardness A (HRB) which is the maximum value of hardness on a first line extending from the center in one direction to the surface of the steel material, a maximum hardness B (HRB) which is the maximum value of hardness on a second line extending from the center to the surface of the steel material in the opposite direction to the first line, and a hardness C (HRB) at the center satisfy the relationship of the following formula (1), and the average hardness in the any cross section is 93 HRB or less. |(C-A)-(C-B)|≦4.0HRB (1)

2. 2. The steel bar according to claim 1, wherein the grain size of ferrite in the metal structure of any cross section is 8.0 or more in terms of average grain size number measured in accordance with JIS G 0551.

3. 2. The steel bar according to claim 1, wherein the arbitrary cross-sectional shape is a circle or a rectangle.

4. 2. The steel bar according to claim 1, wherein the steel is made of any one of SCr, SCM, and Nb-added alloy steel with improved hardenability.

5. 2. The steel bar according to claim 1, wherein the metal structure in any cross section has a ratio of ferrite and pearlite structures of 80% or more.

6. A method for producing a steel bar according to claim 1, A method for manufacturing a bar-shaped steel material, comprising rolling a slab with a rolling mill to form an intermediate product, and introducing the intermediate product having a surface temperature of 1000°C or less into a finishing rolling mill to perform finish rolling.

Citation Information

Patent Citations

  • Production of steel bar stock excellent in cold shearing property

    JP1990209429A

  • Rolled steel bar and its manufacturing method

    JP2005330554A

  • Steel for case hardening having excellent crystal grain coarsening resistance and cold workability and capable of obviating softening and method for producing the same

    JP2006265704A

  • Case hardening steel having excellent crystal grain coarsening resistance and cold workability and in which softening can be obviated, and method for producing the same

    JP2006307271A

  • Case hardening steel having excellent crystal grain coarsening resistance and cold workability and in which softening can be obviated, and method for producing the same

    JP2006307273A